2019
DOI: 10.1111/ppl.13003
|View full text |Cite
|
Sign up to set email alerts
|

Practical aspects of the measurements of non‐photochemical chlorophyll fluorescence quenching in green microalgae Chlamydomonas reinhardtii using Open FluorCam

Abstract: Methods of chlorophyll fluorescence measurements are widely used in the research on photosynthesis and ecophysiology of plants and algae. Among them, a very popular technique is pulse‐amplitude‐modulation (PAM) flourometry, which is simple to carry out, fast and non‐invasive. However, this method is also prone to generate artifacts if the experiments were not planned and executed properly. Application of this technique to algae brings additional complications, which need to be taken into consideration. Some of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…The higher chlorophyll content in the dye-irradiated cultures implied that the dyes facilitated the absorption and transfer of light energy via photosynthesis. These findings supported previous research that demonstrated the enhancement of photosynthetic pigments including chlorophyll, when microalgae were exposed to optimal light conditions (Nawrocki, et al, 2020;Nowicka, 2020).…”
Section: Effects Of Dye-mediated Irradiation On Metabolite Productionsupporting
confidence: 91%
See 2 more Smart Citations
“…The higher chlorophyll content in the dye-irradiated cultures implied that the dyes facilitated the absorption and transfer of light energy via photosynthesis. These findings supported previous research that demonstrated the enhancement of photosynthetic pigments including chlorophyll, when microalgae were exposed to optimal light conditions (Nawrocki, et al, 2020;Nowicka, 2020).…”
Section: Effects Of Dye-mediated Irradiation On Metabolite Productionsupporting
confidence: 91%
“…were not yet acclimated to the light conditions (Nowicka, 2020;Meagher, et al, 2021;Herdean, et al, 2022). However, as the experiment progressed, the Y(NO) yield gradually decreased (> day 4), signifying that the fraction of unregulated energy dissipation played a role during photoacclimation (Yadav, et al, 2020).…”
Section: Effects Of Dye-mediated Irradiation On Photosynthetic Energy...mentioning
confidence: 99%
See 1 more Smart Citation
“…The excess light energy is eliminated by non-photochemical quenching to protect the normal progress of the photochemical reaction (Yong et al, 2018). Therefore, non-photochemical quenching parameters always increase to protect photosynthesis under mild stress or in the early stage of severe stress by quenching (e.g., pH-gradient build-up, LHC 2 phosphorylation and zeaxanthin formation) and recovery (such as a stressadapting D1 protein) mechanisms, but decrease with further damage (Cummings et al, 2018;Nowicka, 2019). Photochemical quenching parameters reflect the photochemical capacity of PSII in the light-adapted state and correspond to the steady-state fraction of oxidized PSII reaction centers (Zulfugarov et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The potential photochemical efficiency (Fv/Fo) was calculated as (Fm-Fo)/Fo, these parameters reflect the potential activity of the PSII [39]. The maximum quantum yield of PSII photochemistry in dark, QYmax = Fv/Fm, reflects the maximum efficiency to transform the light absorbed by PSII [40]. The effective quantum yield of PSII photochemistry in the light, Fv'/Fm' = (Fm'-Fo')/Fm', indicates the primary efficiency at which light absorbed by PSII is used for photochemistry, which is the PSII operating efficiency when all the PSII centers were open (primary quinone electron acceptor-Q A oxidized) [19].…”
Section: Chlorophyll Fluorescence and Growth Performance Parameters M...mentioning
confidence: 99%